AUTO-DYNAMIC INTRAMEDULLARY OSTEOSYNTHESIS FOR FEMUR FRACTURES AND CONSEQUENCES OF INJURIES - P.P. ZUEV; YU.A. BARABASH; I.A. NORKIN; D.V. IVANOV; O.A. KAUTS; K.A. GRAZHDANOV; A.P. BARABASH (Avicenna Tajik State Medical University, 2021)
Objective: The assessment of clinical testing results of the new intramedullary rod which design features neutralize the disadvantages of conventional blocking devices. Methods: The research involved 15 patients with ununited femoral shafts fractures underwent intramedullary revision osteosynthesis with BNB rods. The analysis of surgical management was performed using the standardized system of bone fractures outcomes and their consequences (Standardized Outcome Assessment-1, SOA-1) as well as the modified Radiographic Union Score (mRUS). Results: The examination reveals positive dynamics 2 months after the revision osteosynthesis with BNB rods. The mean rehabilitation rate by the SOA1 was 75.3±0.6 percent, it was 84.0±1.2 percent (p<0.001) in 6 months after the surgery and 90.8±2.7 percent (p>0.05) by the 12th month. Considering mRUS scores, the degree of consolidation of the femoral fracture in patients 2 months after surgery using the BNB rod corresponded to 5.0±0.2 points, to 13.3±0.8 points (p<0.001) in 6 months and to 14.8±1.0 points (p>0.05) by the 12th month. In 1 case (6.7%) out of 15, no union of the fractured fragments was observed. Conclusion: The technical solutions implemented in the BNB intramedullary rod contribute to the autodynamization of the bone-implant system under the action of a controlled load and muscle power on the limb without additional surgical interventions, which makes it possible to shorten the rehabilitation period for patients, resulting in the reduction of treatment expenses for this cohort of patients.